พฤติกรรมผู้นำของผู้บริหารสถานศึกษากับแรงจูงใจในการปฏิบัติงานของครู สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษายะลา เขต 2 - หะแว, นูรียะห์ (Al-HIKMAH Journal, 2021)
Abstract The objectives of this research were 1) to study the level of leadership behavior of the school administrators of Yala Primary Educational Service Area Office 2, 2) to study the level of the motivation of teachers’ work of Yala Primary Educational Service Area Office 2, 3) to compare the level of leadership behavior of the school administrators of Yala Primary Educational Service Area Office 2 classified by variables: gender, educational background, working experience and size of the school, 4) to compare the level of teachers’ motivation of Yala Primary Educational Service Area Office 2 classified by variables, gender, educational background, working experiences and size of the school, 5) to study the correlation between leadership behavior of the school administrators and work motivation on teachers of Yala Primary Educational Service Area Office 2, and 6) to compile problems and suggestions of leadership behavior of the school administrators with work motivation on teachers of Yala Primary Educational Service Area Office 2. The number of 292 teachers, under Yala Primary Educational Service Area Office 2, was research samplings. The research tool was the 4 part questionnaire regarding teachers’ opinion. The percentage, mean, standard deviation were employed for statistical analysis while Scheffe’s Method and Pearson Product Moment Correlation were utilized to test the different value of t-test and F-test The results were as follows: The overall level of leadership behavior of the school administrators under Yala Primary Educational Service Area Office 2 was at a high level. The overall level of work motivation on teachers under Yala Primary Educational Service Area Office 2 was at a high level. The comparison of the differences on the level of leadership behavior of the school administrators under Yala Primary Educational Service Area Office 2 classified by variables of gender, educational background, working experience and the size, as a whole and as an individual aspect were at no difference. The comparison of the differences on the level of the motivation in work on teachers’ under Yala Primary Educational Service Area Office 2 classified by variables of the gender, the educational background, the working experience and the size, as a whole and as an individual aspect, were at no difference. The correlation between the leadership behavior of the school administrators and work motivation on teachers’ under Yala Primary Educational Service Area Office 2, as a whole and as an individual aspect, were at a quite high level. Problems and suggestions regarding the leadership behavior of the school administrators under Yala Primary Educational Service Area Office 2 are that the supervision given solely by the school administrators, and they never listen to the opinions. No caring is given, yet work is assigned only to a particular individual, no follow-up and continuity. The suggestions given here are that the school administrators need to listen to the opinions from various aspect and involve teamwork. Moreover, caring coworkers equally is another suggestion to be considered together with setting the goals for challenging work. Problems and suggestions for work motivation on teachers under Yala Primary Educational Service Area Office 2 are that the school administrators never accept the mistakes from work, not being neutral , unorganized work assignment, no deadlines, and never inspire the teachers for their self-development. The suggestions given here are that the school administrators must build positive attitude towards teachers, being able to solve the problems within a short time and promoting teachers for their future career advancement.